LASER BEAMS : Formation of doughnut and super-Gaussian intensity distributions of laser radiation in the far field using a bimorph mirror. (29th January 2018) - Lylova, A N; Sheldakova, Yu V; Kudryashov, A V; Samarkin, V V
Abstract: We consider the methods for modelling doughnut and super-Gaussian intensity distributions in the far field by means of deformable bimorph mirrors. A method for the rapid formation of a specified intensity distribution using a Shack–Hartmann sensor is proposed, and the results of the modelling of doughnut and super-Gaussian intensity distributions are presented.